STIGMA AND DISCRIMINATION ASSOCIATED WITH TUBERCULOSIS - T.M. KIM; T.CH. CHUBAKOV; A.A. TOKTOGONOVA; K.A. DUSHIMBEKOVA (Avicenna Tajik State Medical University, 2019)
Objective: To study the impact of stigma and discrimination associated with tuberculosis in the Kyrgyz Republic. Methods: The analysis of 135 questionnaires from patients with newly diagnosed tuberculosis respiratory organs being under the supporting phase of anti-tuberculosis treatment from 2012 to 2015. Among the respondents, there were 81 men, 54 women. Results: The average age of the patients was 36.9±3.7 years. It was found that only 12.6±2.9% of respondents noted that they did not experience any fear, anxiety due to the fact that they were diagnosed tuberculosis: this indicator was detected in 14.8±3.9% men and 9.3±3.9% of women. "The fear of infecting the family with tuberculosis", is the most common among all identified fears, this was the case in 71.1% of patients. Each fourth respondent answered that he was hiding the diseases from friends, colleagues, neighbors. Almost as many patients indicated that they were isolated from other family members - 23.5±4.7% of men and 18.5±5.3% of women. A small part of respondents was condemned by family members and neighbors, this was observed in 4.9±2.4% of men and 3.7±2.6% of women. Women more often than men refused to communicate with family members due to illness. Conclusion: Currently, there is a high level of stigma associated with tuberculosis in the Kyrgyz Republic. One of the reasons for this phenomenon is low sanitary literacy of the population. In order to reduce the impact of the stigma associated with tuberculosis, increase the influencing of new cases of tuberculosis, reducing the timing of diagnosis must raise the level of knowledge about tuberculosis, and to increase the importance of family support in the fight against the disease among the population.